2022
DOI: 10.1155/2022/4766305
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Study of Root Canals of Maxillary Molars by Cone-Beam Computed Tomography

Abstract: The aim of this study was to evaluate the root canal morphology of permanent maxillary molars by cone-beam computed tomography (CBCT) using the classifications of Weine et al. and Vertucci and to correlate the findings with sex, age, position in the dental arch, and prevalence of a second canal in the mesiobuccal root (MB2). A total of 414 scans were evaluated, corresponding to 1,000 teeth. The assessment consisted of coronal, axial, and sagittal reconstructions using i-CAT Workstation®. Type 0 was assigned wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Endodontic therapy is more challenging for practitioners since root canal structural patterns differ by ethnicity [ [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. The effective management of periapical infections is crucial for the successful outcome of endodontic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Endodontic therapy is more challenging for practitioners since root canal structural patterns differ by ethnicity [ [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. The effective management of periapical infections is crucial for the successful outcome of endodontic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies utilizing panoramic radiographs and CBCT have consistently investigated impacted maxillary canines [ 29 , 30 , 31 , 32 ] or the root morphology and impaction of the posterior teeth [ 33 , 34 , 35 ]. Previous studies have also reported morphological analyses of impacted maxillary central incisors [ 6 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The existence of the MB2 canal is one of the factors responsible for the morphological complexity of maxillary second molars (Rosaline et al, 2021). Numerous studies in various populations using various methods have shown considerable variation in identifying the MB2 canal in the maxillary second molars (Betancourt et al, 2015;Ghoncheh et al, 2017;Naseri et al, 2018;Kharouf & Mancino, 2019;D'Souza et al, 2021;Magalhães et al, 2022). Therefore, one of the primary reasons an endodontic treatment on maxillary second molars is incomplete might be the failure to detect the MB2 canal (Betancourt et al, 2015;Kharouf & Mancino, 2019).…”
Section: Introductionmentioning
confidence: 99%